Creative Disruption: Technology Innovation, Labour Demand and the Pandemic - Erling Barth; Alex Bryson; Harald Dale-Olsen (Institute of Labor Economics (IZA), 2022)
We utilize a new survey on Norwegian firms' digitalization and technology investments, linked to population-wide register data, to show that the pandemic massively disrupted the technology investment plans of firms, not only postponing investments, but also introducing new technologies. More productive firms innovated, while less productive firms postponed investments. Most innovations were permanent, not due to acceleration of existing plans, thus the pandemic yields longterm influence in directions unanticipated before the pandemic. The new technologies are associated with increased labour demand for skilled workers, and reduced demand for unskilled workers, particularly for the more productive firms.
Keywords: D22; D24; F14; L11; L60; 330; technology investments; digitalization; labour demand; pandemic; COVID-19